Production of the rotifer Brachionus plicatilis (Ploimida: Brachionidae) in a Brazilian coastal lagoon - Maioli Castilho, María Stela (Universidad de Costa Rica, 2000)
Secondary production, density and biomass fluctuations, and some reproductive aspects of the rotifer Brachionus plicatilis were studied weekly for two years in a Brazilian coastal lagoon. Food (and secondarily temperature) seemed to be the main factor involved in the summer increments. In the first summer, a mass mortality of fish caused changes in the phytoplankton, which switched from the dominance of Cyanophyceae to Chlorophyceae and other groups. For two months, production, density and biomass were relatively high until the recovery of the Cyanophyceae dominance. In the second summer, peaks of shorter duration and higher values of production, in comparison to the first one, were found. The contribution of resting eggs hatching, in the first summer, and the increment in parthenogenetic reproduction, in the second summer, would account for the population increases observed. Males and mictic females occurred when densities were high.